Aryl Hydrocarbon Receptor Activation in Intestinal Obstruction Ameliorates Intestinal Barrier Dysfunction Via Suppression of MLCK-MLC Phosphorylation Pathway. Issue 3 (September 2016) - Han, Bin; Sheng, Baifa; Zhang, Zhicao; Pu, Aimin; Yin, Jiuheng; Wang, Qimeng; Yang, Kunqiu; Sun, Lihua; Yu, Min; Qiu, Yuan; Xiao, Weidong; Yang, Hua
ABSTRACT: Background: Accumulating evidence suggests that the aryl hydrocarbon receptor (AhR) plays an important role in the maintenance of the function of the intestinal barrier in patients with inflammatory bowel disease and in mouse models. Intestinal obstruction (IO) is a clinical emergency consisting of severe dysfunction of intestinal barrier function, and whether AhR plays a role in the pathogenesis of IO remains unknown but would be highly significant. Methods: Male C57BL/6 mice were subjected to IO and either treated with AhR endogenous agonist 6-formylindolo [3, 2-b] carbazole (FICZ) or left untreated. Intestinal tissue was harvested after 24 h. Correspondingly, Caco-2 monolayers were treated with FICZ in the absence or presence of hypoxia in vitro or left untreated. The cells were used after 12 h. Results: Damage to the intestinal mucosa was anabatic and intestinal permeability was significantly higher in murine IO and hypoxia-induced Caco-2 models than in controls. Under these conditions the activity of AhR was lower and the fluorescence of zonula occludens-1 (ZO-1) was absent. The increased expression of myosin light chain kinase (MLCK) and phosphorylated MLC (pMLC) indicated that this pathway was open. However, treatment with FICZ caused retention of the tight junction protein ZO-1, alleviated the increase of intestinal permeability, and mitigated epithelial injury. Depletion of AhR by AhR small interfering RNA facilitated the unblocking of the MLCK-pMLC signaling pathway and repressed the protein expression of ZO-1 in vitro . Conclusion: AhR activation can ameliorate epithelial barrier dysfunction induced by IO through the suppression of MLCK-pMLC signaling, suggesting that AhR agonist may be a suitable means of addressing this condition.